2019
DOI: 10.1177/2333794x19840361
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Health Insurance Program Expansions: What Works for Families?

Abstract: We examine the impact of Children’s Health Insurance Program (CHIP) eligibility expansions 1999 to 2012 on child and joint parent/child insurance coverage. We use changes in state CHIP income eligibility levels and data from the Current Population Survey Annual Social and Economic Supplement to create child/parent dyads. We use logistic regression to estimate marginal effects of eligibility expansions on coverage in families with incomes below 300% federal poverty level (FPL) and, in turn, 150% to 300% FPL. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…(33,34). Medicaid demonstration programs are testing different payment and delivery models that include broadening services to health-related needs such as providing community health workers to assist families with housing, food and income (35,36). The recently introduced Social Determinants Accelerator Act of 2019 would convene a federal inter-agency technical advisory council to identify opportunities for state and local governments to coordinate funding and administration of federal programs that may be underutilized or unknown.…”
Section: Discussionmentioning
confidence: 99%
“…(33,34). Medicaid demonstration programs are testing different payment and delivery models that include broadening services to health-related needs such as providing community health workers to assist families with housing, food and income (35,36). The recently introduced Social Determinants Accelerator Act of 2019 would convene a federal inter-agency technical advisory council to identify opportunities for state and local governments to coordinate funding and administration of federal programs that may be underutilized or unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The initial phase evaluation results show challenges in areas such as having an adequate work force to address social needs, lack of standardization, adequate data systems, and closing referral loops between health care and community services (30,31). Medicaid demonstration programs are also testing different payment and delivery models that can include broadening services to health-related needs such as providing community health workers to assist families with housing, food and income (32,33). The recently introduced Social Determinants Accelerator Act of 2019 would convene a federal inter-agency technical advisory council to identify opportunities for state and local governments to coordinate funding and administration of federal programs that may be underutilized or unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Child health insurance programs have extended well-child and illness care to millions of uninsured families throughout the U.S. (12), making more apparent the many unaddressed physical health and social needs they face. Latinx families in the U.S. have the highest uninsured rates, compared to other racial or ethnic groups, with only 49% reporting insurance coverage in 2017 (13).…”
Section: Introductionmentioning
confidence: 99%
“…There is preliminary evidence of similar models in the area of increasing families' access to resources and improving socio-economic circumstances. For example, using the WE CARE model to systematically screen and refer families to services, results of a randomized control trial including 336 mothers in 8 community health centers showed that mothers who received the intervention were more likely to be employed, less likely to be homeless, and to have accessed at least one resource compared with mothers who did not receive the intervention (32) (35,36). The recently introduced Social Determinants Accelerator Act of 2019 would convene a federal inter-agency technical advisory council to identify opportunities for state and local governments to coordinate funding and administration of federal programs that may be underutilized or unknown.…”
Section: Discussionmentioning
confidence: 99%